A USER-CENTERED DIGITAL REPOSITORY: DESIGNING AND EVALUATING HOBBYHAVEN FOR COLLECTORS (Journal of Digital System Development, 2025)
Collecting physical and digital items has become increasingly popular, but many collectors struggle with keeping their collections organised, accessible, and easy to manage. Traditional methods, such as manual record-keeping or essential digital tools, often fail to meet their needs. This study introduces HobbyHaven, a web-based repository designed to simplify collection management. The platform allows users to store, organise, and track their collectables more efficiently. The goal is to create a simple, intuitive, and customisable system, making it accessible to collectors of all experience levels. HobbyHaven was developed using the Waterfall methodology, which follows a structured approach that includes gathering user requirements, designing the system, and building a functional prototype. To evaluate its usability, we applied the Website Analysis and Measurement Inventory (WAMMI) framework, which assesses key factors such as attractiveness, ease of use, helpfulness, efficiency, and learnability. A total of 35 participants tested the system and provided feedback through a five-point Likert scale questionnaire. The results showed high user satisfaction, particularly with navigation (85.8%) and helpfulness (85.7%), indicating that users found the platform well-structured and easy to use; however, some areas required improvement. For instance, only 45.7% strongly agreed that the visual design was appealing. In comparison, 37.1% felt neutral about the need for better introductory guidance, and a further 37.1% agreed that some features were difficult to locate. HobbyHaven has the potential to significantly enhance collection management by providing an organised, user friendly, and accessible platform. Reducing reliance on outdated methods allows collectors to track and manage their items more effectively, fostering knowledge sharing and community engagement. Its open-access feature enables users to explore collections without requiring registration, making it more inclusive. With further improvements—such as AI-driven categorisation and integrated social networking features—HobbyHaven could evolve into a leading digital repository for collectors, transforming how collections are documented, shared, and preserved.